Postradzieckie wersje pamięci w najnowszej literaturze ukraińskiej - Pukhonska, Oksana (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
For the modern society it is very important to find some explanations of the historical events of the 20th century. The matter is that those events, which were so destructive with theirs totalitarian occupation, mass killing of the whole nations that they had a great influence on the behavior of people nowadays. It is extremely important that different cultural groups try to retrieve memory, which was lost in the result of different historical conditions. Literature has large contribution to this process by creating the artistic environment where the forgotten world can be remained with the help of memory. In the process of reflecting history modern literature very often creates the space of the retained and recovered memory. Arts also becomes the so-called therapy for societies, which have been injured as a result of genocide against the whole nations.